NGF receptor TrkAd5: therapeutic agent and drug design target. (21st July 2006) - Dawbarn, D.; Fahey, M.; Watson, J.; Tyler, S.; Shoemark, D.; Sessions, R.; Zhang, R.; Brady, L.; Willis, C.; Allen, S.J.
Abstract : Biochemical studies have shown that domain 5 of the TrkA (tropomyosin receptor kinase A) receptor is involved in the binding of NGF (nerve growth factor). Crystallographic studies have confirmed this, demonstrating that one homodimer of NGF binds to two TrkAd5 molecules. TrkAd5 has been made recombinantly in Escherichia coli, purified and shown to bind NGF with picomolar affinity. We have used the co-ordinates of the crystal structure of the NGF–TrkAd5 complex to screen approximately two million compounds in silico for the identification of small molecule agonists/antagonists. Selected hits were shown to be active in an in vitro ligand-binding assay; structure–activity relationships are now being investigated. In addition, TrkAd5 has been shown to be efficacious in preclinical models of inflammatory pain and asthma by the sequestration of excess levels of endogenous NGF, and therefore represents a novel therapeutic agent.